2016
DOI: 10.1038/srep27409
|View full text |Cite
|
Sign up to set email alerts
|

Viable offspring obtained from Prm1-deficient sperm in mice

Abstract: Protamines are expressed in the spermatid nucleus and allow denser packaging of DNA compared with histones. Disruption of the coding sequence of one allele of either protamine 1 (Prm1) or Prm2 results in failure to produce offspring, although sperm with disrupted Prm1 or Prm2 alleles are produced. Here, we produced Prm1-deficient female chimeric mice carrying Prm1-deficient oocytes. These mice successfully produced Prm1+/− male mice. Healthy Prm1+/− offspring were then produced by transferring blastocysts obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 61 publications
4
54
1
1
Order By: Relevance
“…The latter is supported by Takeda et al ., who were able to generate offspring from Prm1 +/− males by in vitro fertilization of zona-free oocytes, although chromatin integrity of those sperm was severely affected50. Nontheless, strong sperm DNA degradation observed in Prm2 -deficient animals most likely prohibits successful reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is supported by Takeda et al ., who were able to generate offspring from Prm1 +/− males by in vitro fertilization of zona-free oocytes, although chromatin integrity of those sperm was severely affected50. Nontheless, strong sperm DNA degradation observed in Prm2 -deficient animals most likely prohibits successful reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined whether this is a defect in the self-assembly of sperm or a built-in quality control mechanism triggering a self-destructing program. Of note, impaired sperm motility is a common phenotype of Prm1, Prm2, Tnp1 , and Tnp2 knockout mice2950545559.…”
Section: Discussionmentioning
confidence: 99%
“…So far, deletion of the coding sequence of one allele of either protamine‐1 or protamine‐2 has resulted in male sterility despite the presence of spermatozoa (Cho et al., ). In subsequent studies, protamine‐1‐deficient mice (only Prm1 +/− , not Prm1 −/− ) have been reported to be healthy, but sterile (Takeda et al., ). Their sperm exhibited a high level of DNA fragmentation and decreased motility.…”
Section: Perspectivementioning
confidence: 99%
“…Via in vitro fertilization (IVF) healthy Prm1(+/−) offspring were produced demonstrating that spermatozoa lacking Prm1 can fertilize and produce viable embryos. However a detailed survey of the offspring showed midification in expression profiles [135]. …”
Section: Sperm Nuclear/dna Alterations Have Many Facesmentioning
confidence: 99%